2010
DOI: 10.1002/ajmg.a.33524
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 16q21 → qter: Seven‐year follow‐up of a girl with unusually long survival

Abstract: The 16q21 --> qter duplication is a chromosomal abnormality rarely found in liveborn infants, with only four published cases. We report here on the 7-year follow-up of a female patient with trisomy 16q21 --> qter due to a maternal balanced translocation t(4;16)(q35.2;q21). The patient shows severe mental retardation, congenital heart malformations, nephropathy, and other congenital anomalies. The derivative chromosome was characterized by GTG banding, fluorescent in situ hybridization (FISH) with different BAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The distal fragile site of the long arm of chromosome 16 is commonly reported to be located between 16q21 and 16q22, as observed in our case [ 18 20 ]. Table 1 describes the cytogenetic and phenotypic data of the proband in comparison with previously reported cases with trisomy 16q [ 10 , 13 – 17 , 21 – 25 ]. Most of the affected children had abnormal, yet non-specific craniofacial features with flat nasal bridge, small and downslanting palpebral fissures and low set ears which were also observed in the present case.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The distal fragile site of the long arm of chromosome 16 is commonly reported to be located between 16q21 and 16q22, as observed in our case [ 18 20 ]. Table 1 describes the cytogenetic and phenotypic data of the proband in comparison with previously reported cases with trisomy 16q [ 10 , 13 – 17 , 21 – 25 ]. Most of the affected children had abnormal, yet non-specific craniofacial features with flat nasal bridge, small and downslanting palpebral fissures and low set ears which were also observed in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic abnormalities such as congenital heart defects, renal abnormalities, lung abnormalities and gall bladder agenesis were also reported [ 12 ]. More specifically, in patients with trisomy of the distal segment of the long arm of chromosome 16, the cardiac defects were uncommon [ 13 – 17 ]. These patients survived longer, except one patient [ 14 ] who died 22 days after birth despite the absence of cardiac defects or other systemic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the published data has shown that most of the patients with partial trisomy 16 have heart defects and patients with larger trisomic segments have more incidence of congenital heart defects. 5 Common congenital heart diseases reported with partial trisomy 16 include ventricular septal defect, atrial septal defect (ASD), patent ductus arteriosus (PDA), coarctation of aorta, and interatrial septum aneurysm [6][7][8][9][10][11][12] (►Table 1). However, Mishra et al 13 for the first time had reported a case of partial trisomy 16q21-qter with complex cardiac abnormalities that included double outlet right ventricle, PDA, ASD, pulmonary stenosis, and bilateral superior vena cava.…”
Section: Discussionmentioning
confidence: 99%